Molecular Species Identification of Three Deer Samples Using 16S rRNA Gene Sequencing - Manoj G. Ghuge; Deepak M. Gaikwad; Shudodhan Ratnparke; Vitthal Kharat; Shubham Malekar (The Bioscan, 2026)
Molecular identification of animal species from trace evidence is critical in wildlife conservation and forensics. This study reports the successful species identification of three hair follicle samples (MG1, MG2, and MG3) using the 16S ribosomal RNA (rRNA) gene marker. The 16S rRNA gene, a conserved sequence with variable regions, serves as a standard for classification and identification of microorganisms and is also used in mitochondrial DNA studies for eukaryotes. DNA was extracted from the samples, and the 16S rRNA gene fragment was amplified and sequenced. Bioinformatics analysis, including BLAST and phylogenetic methods, assigned the samples to three distinct species of the Cervidae and Bovidae families. Sample MG1 was identified as Axis porcinus (Hog Deer), MG2 as Antilope cervicapra (Blackbuck), and MG3 as Rusa unicolor (Sambar Deer). These results demonstrate the efficacy of 16S rRNA sequencing from non-invasive samples like hair follicles for accurate species determination. Keywords animal species, rRNA, 16S ribosomal.